Persepsi Wartawan Terhadap Kualitas Berita di Media Massa Kota Malang - M Nurdiyana; Fathul Qorib (Yayasan Lentera Avanya Nagari, 2023)
The development of mass media in the city of Malang is very rapid. This can be seen from the emergence of various mass media in the city of Malang. News is inseparable from the influence of a journalist because he is an information seeker and the person who writes the news. Therefore, the purpose of this study is to determine the journalists' perceptions of the quality of news in Malang. This study used qualitative research methods. In this study there were eight informants who worked in the mass media in Malang. Data collection techniques used by researchers are interviews and documentation. Researchers used three research methods namely, data reduction, data presentation, drawing conclusions and verification. The results of the study require that in general journalists' perceptions of the quality of news in the city of Malang are the same, which is quite good, with a few small notes of problems that make the news not quality. In addition, the factors that influence journalists' perceptions of the quality of the news are external factors, namely the organization of the press that is followed.